Photograph of Alexander Wheelock Thayer - Carl Günther (photographer)::::::::::::::: (Germany; Berlin; Carl Günther, 2023)
Studio portrait photograph of Alexander Wheelock Thayer by Carl Günther in Berlin, mounted on card with Günther's imprint and address at "Behrenstrasse 24 in Siechen'schen Hause" on front and back; signed "Alexander Wheelock Thayer" and dated "January 1888" in ink in an unidentified hand on verso.